Hydrogen Sulfide Delivery to Enhance Bone Tissue Engineering Cell Survival - Soheila Ali Akbari Ghavimi; Trent J. Faulkner; Rama Rao Tata; August J. Hemmerla; Samantha E. Huddleston; Farnoushsadat Rezaei; Ethan S. Lungren; Rui Zhang; Erin E. Bumann; Bret D. Ulery (MDPI AG, 2024)
Though crucial for natural bone healing, local calcium ion (Ca2+) and phosphate ion (Pi) concentrations can exceed the cytotoxic limit leading to mitochondrial overload, oxidative stress, and cell death. For bone tissue engineering applications, H2S can be employed as a cytoprotective molecule to enhance mesenchymal stem cell (MSC) tolerance to cytotoxic Ca2+/Pi concentrations. Varied concentrations of sodium hydrogen sulfide (NaSH), a fast-releasing H2S donor, were applied to assess the influence of H2S on MSC proliferation. The results suggested a toxicity limit of 4 mM for NaSH and that 1 mM of NaSH could improve cell proliferation and differentiation in the presence of cytotoxic levels of Ca2+ (32 mM) and/or Pi (16 mM). To controllably deliver H2S over time, a novel donor molecule (thioglutamic acid-GluSH) was synthesized and evaluated for its H2S release profile. Excitingly, GluSH successfully maintained cytoprotective level of H2S over 7 days. Furthermore, MSCs exposed to cytotoxic Ca2+/Pi concentrations in the presence of GluSH were able to thrive and differentiate into osteoblasts. These findings suggest that the incorporation of a sustained H2S donor such as GluSH into CaP-based bone graft substitutes can facilitate considerable cytoprotection, making it an attractive option for complex bone regenerative engineering applications.